2006
DOI: 10.1093/nar/gkl132
|View full text |Cite
|
Sign up to set email alerts
|

Structural model for the multisubunit Type IC restriction-modification DNA methyltransferase M.EcoR124I in complex with DNA

Abstract: Recent publication of crystal structures for the putative DNA-binding subunits (HsdS) of the functionally uncharacterized Type I restriction–modification (R-M) enzymes MjaXIP and MgeORF438 have provided a convenient structural template for analysis of the more extensively characterized members of this interesting family of multisubunit molecular motors. Here, we present a structural model of the Type IC M.EcoR124I DNA methyltransferase (MTase), comprising the HsdS subunit, two HsdM subunits, the cofactor AdoMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 71 publications
1
24
0
Order By: Relevance
“…Based on our predictions and supporting experimental data, we hypothesize that MmeI and other type IIC REases with similar domain architectures are more closely related to type I RM systems than to other type II REases. The molecular model of MmeI presented in this work corresponds to just one-half of the type I enzyme structure (42), suggesting that head-to-head dimerization may be required for its function. This inference agrees with the strong preference of MmeI for using oppositely oriented sites as substrates (e.g., the ability to damage the fully unmodified E. coli genome containing 1,201 MmeI sites, 111 in the forward and 1,090 in the reverse orientation), compared to single or tandemly repeated sites (an inability to cleave a newly replicated genome with one unmethylated strand, in which all unmodified MmeI sites are in the same orientation).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Based on our predictions and supporting experimental data, we hypothesize that MmeI and other type IIC REases with similar domain architectures are more closely related to type I RM systems than to other type II REases. The molecular model of MmeI presented in this work corresponds to just one-half of the type I enzyme structure (42), suggesting that head-to-head dimerization may be required for its function. This inference agrees with the strong preference of MmeI for using oppositely oriented sites as substrates (e.g., the ability to damage the fully unmodified E. coli genome containing 1,201 MmeI sites, 111 in the forward and 1,090 in the reverse orientation), compared to single or tandemly repeated sites (an inability to cleave a newly replicated genome with one unmethylated strand, in which all unmodified MmeI sites are in the same orientation).…”
Section: Discussionmentioning
confidence: 90%
“…1A, we found that the C-terminal region of MmeI (aa ϳ610 to 919) exhibits similarity to the target recognition domains (TRDs) involved in substrate recognition of the type II MTase M.TaqI (1g38; HHsearch P ϭ 1.5E-05; FFAS [21] score, Ϫ10.3) and of the HsdS subunit of putative type I enzymes: ORF MJ0130 from Methanocaldococcus jannaschii (1yf2; e.g., mGenTHREADER [36] score, 0.3) and ORF MG438 from Mycoplasma genitalium (1ydx; e.g., FFAS score, Ϫ4.96). Importantly, we could find only one copy of the putative TRD in the MmeI amino acid sequence (such as in M.TaqI, which methylates adenosine in the target TCGA), whereas most of the HsdS subunits of type I enzymes comprise two TRDs that effectively recognize two DNA sites in an inverse orientation, separated by a nonspecific sequence of fixed length (24,42). The putative TRD in the MmeI sequence is followed by a region (aa 820 to 919) comprising three predicted helices, for which we could not detect any obvious relationship to known REases or MTases or to any known protein structures.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy, in this respect, that a process of deassembly of the enzymes occurs after DNA cleavage, and some of the subunits-although not all and depending on the particular type I RM enzyme-can be reused (Roberts et al 2011;Simons and Szczelkun 2011). Lapkouski et al (2009) proposed a more speculative atomic model of EcoR124I using their structure of HsdR, a postulated DNA path across the subunit, and an early, incomplete model of the MTase core (Obarska et al 2006). Although the current models and their model share much in common, there are two main differences; namely, the orientation of the HsdR with respect to the MTase core, and the path taken by the DNA.…”
Section: Structure Of Type I Restriction Enzymesmentioning
confidence: 99%
“…In contrast to the situation with type II restriction enzymes, it is only very recently that partial atomic structures for type I RM subunits have emerged (Calisto et al 2005;Kim et al 2005;Obarska et al 2006;Obarska-Kosinska et al 2008;Kennaway et al 2009;Lapkouski et al 2009;Uyen et al 2009;Taylor et al 2010;Gao et al 2011), and their mechanisms, which most dramatically involve the translocation of thousands of base pairs of DNA with the formation of supercoiled loops (Yuan et al1980;Endlich and Linn 1985;Studier and Bandyopadhyay 1988;García and Molineux 1999), still present many questions. The type I RM enzymes are complex structures with two HsdR restriction (R) subunits, two HsdM modification (M) subunits, and one HsdS sequence specificity (S) subunit (Murray 2000;Loenen 2003), each with a number of domains (Supplemental Fig.…”
mentioning
confidence: 99%
“…Although, to date, there is no actual protein structure for either HsdS or the MTase of the EcoR124I system, the recent crystallization of related HsdS subunits (12,50) has confirmed the circular structure proposed for HsdS and allowed us to model in silico not only the HsdS subunit of EcoR124 but also the MTase of this enzyme (62). One of the interesting observations from this structural model was the ability of the model to allow a prediction for the mechanism of DNA binding.…”
Section: The Central Conserved Region Of Hsdsmentioning
confidence: 86%